An Analysis of Factors Causing Students’ Difficulties in Mastering English Vocabulary Through the Implementation of the Independent Curriculum at SDN Gunung Borok - Wawan Sapudra (Universitas Qamarul Huda Badaruddin, 2025)
This study investigates the factors contributing to students’ difficulties in mastering English vocabulary under the implementation of the Independent Curriculum (Kurikulum Merdeka) at SDN Gunung Borok. Using a descriptive qualitative approach, data were collected through classroom observations, interviews with teachers and students, and documentation of lesson plans and assignments. Findings reveal that internal factors such as low motivation, limited basic vocabulary, and pronunciation anxiety hinder students’ progress. External challenges include traditional memorization-based teaching methods, limited use of learning media, and minimal support from families and the surrounding environment. Although the Independent Curriculum emphasizes flexible, student-centered, and contextual learning, its implementation remains suboptimal due to constraints in teacher training, time, and facilities. The study concludes that enhancing vocabulary mastery requires innovative teaching strategies such as project-based learning, educational games, visual and auditory media, and greater parental involvement. Recommendations include teacher professional development, provision of learning resources, and stronger collaboration between school and home environments.